Broadband‐Tunable Third‐Harmonic Generation Using Phase‐Change Chalcogenides. Issue 10 (12th June 2022) - Zhu, Muliang; Abdollahramezani, Sajjad; Li, Chentao; Fan, Tianren; Harutyunyan, Hayk; Adibi, Ali
Abstract : Despite remarkable progress in passive nonlinear nanophotonics, dynamically controlled ultracompact nonlinear optical sources with high efficiency remain elusive. Nonvolatility, large refractive index contrast between amorphous and crystalline phases, low thermal threshold for crystallization, and particularly high‐third‐order nonlinear optical susceptibility of phase‐change alloy Ge2 Sb2 Te5 (GST) make it a promising candidate for active subwavelength metaphotonic structures for realization of third‐harmonic generation (THG) devices. Herein, a GST‐based asymmetric Fabry–Perot cavity is numerically designed and experimentally demonstrated to show a dynamically reconfigurable structure with a large shift of the THG resonant band. In addition, continuous resonant spectral shifting bridged by a precisely controlled semicrystalline phase of GST is realized. Tunable THG with the fundamental wavelength ranging from 1150 to 1400 nm is presented, which corresponds to a broadband THG source in the violet‐blue visible wavelength range. Herein, the potential of GST subwavelength structures as a reliable platform for realization of the broadband‐tunable frequency‐conversion sources for applications such as THG microscopy and optical communication is indicated. Abstract : A new platform is demonstrated based on a subwavelength asymmetric Fabry–Perot cavity structure for broadband‐tunable third‐harmonic generation (THG) by using the conveniently controllable phase‐change material germanium antimony telluride. The structure paves the way for the design of nonlinear nanophotonic structures with improved efficiency and functionality for a wide range of applications, such as a combined band‐and‐phase modulation for THG microscopy.